An Assessment of Forage Selection by Giraffe Introduced into Umfurudzi Park, Northern Zimbabwe. (24th July 2018) - Munyaka, Takunda V.; Gandiwa, Edson
Abstract : Giraffe ( Giraffa camelopardalis ) is one of the flagship herbivore species in the savanna ecosystem and is of high conservation value. Management of the species under diversified ecosystems, particularly, their introduction in new ecosystems is of great concern, given that limited information is available of how the species acclimatizes to new ecosystems and which forage species it selects. The objectives of the present study were to (i) identify woody plant species selected by the recently introduced giraffes and (ii) determine whether there were differences in woody plant diversity between the dry and wet seasons in Umfurudzi Park, northern Zimbabwe. Forage selection and woody composition data were collected from a herd of giraffe between May and December 2016, using the focal observation method in an enclosure within the study area. A total of 106 observation plots were established. Our results showed that 12 woody plant species comprising six families were selected from a total of 29 woody plant species recorded in the study area. Giraffe showed a higher preference of the selected species in the dry season than in the wet season. In contrast, no significant differences were recorded in terms of forage availability and woody vegetation diversity between seasons. In conclusion, our results suggest that plant phenology, particularly, presence of leaves on plants influences giraffe feed preferences. Establishing long-term monitoring plots to determine woody vegetation utilisation by giraffes is valuable as a way to monitoring habitat utilisation by the species.